A just transition to a green economy: evaluating the response of Australian unions - Goods, Caleb (National Institute of Labour Studies, 2013)
Many policymakers, unions, and businesses have embraced the idea of green jobs and a green economy. This enthusiasm for environmentally sound job creation received a significant shot in the arm at the end of 2008, in the context of the global financial crisis, as an important element in the solution to the world’s economic and ecological concerns. The connection between work and combating environmental problems is however an area of significant contestation. This has resulted in highly varied understandings of what constitutes a green job and a just transition to a green economy. This article scrutinises the response of the Australian Council of Trade Unions—as the peak union body in Australia—and three specific unions to the challenge of transiting from the world of work towards an ecologically sustainable footing.